Regular BTZ black holes from an infinite tower of corrections - Fernandes, Pedro Goncalo da Silva (Physics letters, 2025)
We explore 2+1-dimensional scalar-tensor theories derived from well-defined dimensional regularizations of the Lovelock invariants. In the limit where an infinite series of corrections is included, we obtain theories that admit fully regular black hole solutions. We analyze the properties of these regular black holes, investigate geodesics in these spacetimes, and examine the tidal forces, finding they remain finite everywhere.